Maternal and fetal outcome of Placenta Previa at a tertiary centre in North Kerala, India - C., Mohammed Sidhiq (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Placenta previa is defined as placenta that is implanted somewhere in the lower uterine segment either over or very near the internal cervical os. Placenta previa and coexistent accrete syndromes contribute substantively to maternal and perinatal morbidity and mortality. Methods: This study was conducted in the Department of Obstetrics and Gynaecology during the period from June 2016 to May 2017 including antenatal patients of 24 weeks of gestation regardless of their parity. They would be selected from the same O.P day as that of case in a 1:4 case: control manner. Statistical analysis was done using SPSS version 16.0 for Windows. Results: Age, booking status, Gestational age at delivery and gravidity was comparable between the two groups. The risk for placenta praevia was more among patients with a previous history of CS. Risk for antepartum bleeding was significantly higher among cases of placenta praevia. CS rate and proportion of patients who required blood transfusion was significantly high among cases. Intraoperative and postoperative complications were significantly higher among cases. There was no significant difference in neonatal death rate and NICU admission rate between the two groups. Conclusions: Incidence of placenta previa is 0.78%. There is significant association with placenta previa and maternal morbidity, first trimester and second trimester bleeding increased blood transfusions, need for caesarean section, prolonged hospital stay, previous caesarean section, previous dilatation and curettage, placenta accreta, postoperative complications and NICU admission. Measures to reduce the primary caesarean section rate should be adopted.